An interpretation of the organ symphonies of Louis Vierne (1870–1937) with specific reference to his Methode d Orgue - Coetzee, Lourens Erasmus (Stellenbosch : Stellenbosch University, 2020)
Thesis (MPhil)--Stellenbosch University, 2020.